Medicine contamination by the nursing team - Santo, Thyego Mycell Moreira [UNESP]; Godoy, Ilda [UNESP]; Reyes, Davi Rafael Abreu [UNESP] (My University, 2019)
Introduction: Within the health unit, the main adversities associated with contamination affect the patient, and there are flaws in the techniques that can put people's lives at risk. Objective: To identify the main problems associated with the contamination of medicines by the nursing team in the hospital environment. Methods Integrative review as a way to include relevant studies on the subject under analysis. The selected databases were SCOPUS, PubMed Central: PMC, Web of Science/Main Collection, Scielo, Lilacs, and CINAHL (EBSCO). After applying the criteria proposed in the study, 123 articles were identified, out of which number only seven met the inclusion and exclusion criteria for the analysis: two SciELO papers, two from PubMed, one from Web of Science, one from Lilacs, and one from CINAHL. Conclusions: The results showed that contamination of medications is associated with the nursing team and the local area for the medication preparation. The most representative errors include: manipulation and lack of aseptic care. These factors increase the risk for contamination and put patient safety at risk, which makes evident the need to adopt effective and continuous pharmacological education measures among the nursing team.
La contaminación de medicamentos por el equipo de enfermería
Keywords: Care; Medicine contamination; Nursing staff; Review